2016
DOI: 10.1111/ajt.13816
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting the Notch Pathway to Prevent Rejection

Abstract: Immune rejection is mediated by a complex interplay of cellular and humoral mechanisms. Current therapeutic strategies, which rely on global immunosuppression, can result in serious complications and are not completely effective. Notch signaling is a cell-to-cell communication pathway that plays an important role during T cell development and in the regulation of peripheral immune responses. Initial work, performed mainly through gain-of-function approaches, paradoxically identified Notch as an inducer of tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…GVHD is the life-threatening consequence of an alloimmune response following bone marrow transplantation, whereby donor T cells attack recipient tissues [82]. We found dramatic protection against GVHD in MHC-mismatched transplants when Notch signalling was blocked in donor T cells via either conditional DNMAML expression or loss of RBP-Jκ [58,59].…”
Section: Notch Signalling Impacts Mature T Cell Functionmentioning
confidence: 99%
“…GVHD is the life-threatening consequence of an alloimmune response following bone marrow transplantation, whereby donor T cells attack recipient tissues [82]. We found dramatic protection against GVHD in MHC-mismatched transplants when Notch signalling was blocked in donor T cells via either conditional DNMAML expression or loss of RBP-Jκ [58,59].…”
Section: Notch Signalling Impacts Mature T Cell Functionmentioning
confidence: 99%
“…Notch signaling plays an important role in the tumor biology, including cell differentiation, proliferation, apoptosis, migration and invasion [ 7 10 ]. Increasing reports demonstrated that deregulation of Notch1 signaling can be observed in diverse tumor types, such as cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Future directions of transplant research focus on attempting to minimize the immune response by inhibiting aspects of these various mechanisms. An example of an immunomodulatory target is the Notch signaling pathway (65). The Notch pathway is a cellto-cell communication cascade that plays an important role during T cell development and in the regulation of innate lymphoid cells, B cells, and dendritic cells (66).…”
Section: Future Directionsmentioning
confidence: 99%
“…The Notch pathway is a cellto-cell communication cascade that plays an important role during T cell development and in the regulation of innate lymphoid cells, B cells, and dendritic cells (66). The signaling pathway is a central mediator of T cell reactivity to allografts (65). Recent studies have shown that inhibition of the Notch pathway in animal models can reduce both allograft rejection (67) and graft vs. host disease (68).…”
Section: Future Directionsmentioning
confidence: 99%